Performing hybridity : impact of new technologies on the role of teacher-librarians ; a report of research conducted under a QUT Scholarship in the Professions grant - Mallan, Kerry; ScienceDirect eBooks (Wagga Wagga, N.S.W. : Centre for Information Studies, Charles Sturt University : Queensland University of Technology, Centre for Language, Literacy and Diversity, 2002)
This publication was the outcome of a research project undertaken by a team of researchers from Queensland University of Technology and Brisbane Catholic Education Office throughout 1999-2000. The report was originally distributed to a limited number of participants and others considered stakeholders in the fields of education and teacher-librarianship. The publication of the report reflects the interest shown in the project around Australia. The research focused on the impact of new technologies on the day-to-day lives of teacher-librarians, and revealed information that has significant relevance for the training, professional development and infrastructure support for teacher-librarianship. This research is significant as it provides a sound and scholarly approach to the research topic and provides the field and others associated with schooling and teacher-librarianship with documented accounts of the contributions of teacher-librarians, the obstacles they face, and the way technology is affecting their personal and professional lives. Performing Hybridity would be of interest to the teacher-librarianship and general education community. The results of the research are not state or site specific and are applicable to other states in Australia. It is important for administrators and policy makers in state, catholic and independent systems as an information source for staff planning and development, and resourcing. The publication also has value for tertiary institutions offering courses in teacher-librarianship and more general librarianship programs.
Series title in CIP verso title page only.
Includes bibliographical references.
Print version record.
Elsevier
Keywords: Teacher-librarians -- Effect of technological innovations on -- Australia; School librarians -- Effect of technological innovations on -- Australia; School libraries -- Australia -- Automation; SOCIAL SCIENCE -- General; Electronic books